SMART CONTRACT: INNOVATION OF CONTRACT LAW OR FICTION OF THE DIGITAL ENVIRONMENT - Slobodska, Iryna; Tkachenko, Veronika (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: identification of areas of application, limits of opportunities and advantages on the way to implementation and improvement of the use of smart contracts as an alternative to civil law agreement. Methods of research: dialectical, deduction, induction, comparative - legal research, system - structural, formal-dogmatic, method of analogy, functional, comparative-legal, legal modeling. Results: defining the scope, scope and benefits on the way to implementing and improving the use of smart contracts as an alternative to civil law agreement. Discussion: modern civil law relations, which have moved to the digital environment, as the development of technology and the development of appropriate legal support has allowed contract law to obtain an updated form of contract, called «smart contract». Smart contract is cost-effective and simpler in terms of concluding and fulfilling obligations. The innovation combines the interaction of advanced technologies based on blockchain and civil law relations, which have begun to change due to the development of the digital environment. Comparing a reasonable agreement with a traditional written agreement shows an increase in the use and implementation of blockachain technologies and reasonable agreements that work on the above technology instead of concluding a standard written agreement. Therefore, it is necessary to consider in detail the innovation and identify ways to implement and improve the use of smart contracts as an alternative to civil law.